2015
DOI: 10.1016/j.comppsych.2014.05.018
|View full text |Cite
|
Sign up to set email alerts
|

The underlying role of posttraumatic stress disorder symptoms in the association between intimate partner violence and deliberate self-harm among African American women

Abstract: African American women are at heightened risk for intimate partner violence (IPV) and its negative consequences, including health-compromising behaviors. Deliberate self-harm (DSH) is one clinically-relevant behavior that has been understudied among African American women generally and those with exposure to IPV in particular. To date, no studies have examined factors that may account for the relationship between IPV and DSH. Therefore, the goal of the present study was to examine the intercorrelations among I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 91 publications
0
26
1
2
Order By: Relevance
“…104 Although the majority of PIPV research has focused primarily on women, 105 it was found that men also experience mental health problems associated with PIPV. 103,106 It is estimated that more than half of PIPV events are not reported to the police, 107 suggesting the need for intervention efforts aimed outside the realm of law enforcement.…”
Section: Discussionmentioning
confidence: 99%
“…104 Although the majority of PIPV research has focused primarily on women, 105 it was found that men also experience mental health problems associated with PIPV. 103,106 It is estimated that more than half of PIPV events are not reported to the police, 107 suggesting the need for intervention efforts aimed outside the realm of law enforcement.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies by Weiss and colleagues (Weiss et al ., ; Weiss, Dixon‐Gordon, Duke and Sullivan, ) sought to explain the mediating factors which underlie the relationship between IPV and self‐harm. Weiss et al .…”
Section: Overview Of Key Findingsmentioning
confidence: 99%
“…Examples include substance use (James et al, 2014), risky sexual behaviors (Weiss et al, 2014), and deliberate self-harm (Weiss et al, 2015a). Indeed, a study on Veterans receiving treatment for PTSD indicated that a significant number of deaths were related to substance use, suicide, and homicide (Drescher et al, 2003).…”
Section: Introductionmentioning
confidence: 99%